The aesthetic look of affect: reterritorializing Rio de Janeiro - Torraca, Lia Beatriz Teixeira (Pontifícia Universidade Católica de São Paulo, 2020)
This article seeks to present the aesthetic look of affection as a possibility to sensitize and reprogram social perception in Rio de Janeiro based on the perspective of the Shantytown. This is a technique to "make you see", to "transform looking into seeing" and to "make you act on" through the photographic experience - an alternative to reimagine the city from another perspective and to be able to reconfigure the image of Rio de Janeiro and its relations through the virtualization and projection of photographic images produced in the Shantytown, that is, a resource to reterritorialize the city. This proposal was built on the concept of deterritorialization proposed by Pierre Lévy and on Josep Català Domènech’s complex image theory, having the “Phenomenology of Perception” by Maurice Merleau-Ponty as the methodological reference.